The Influence of Auditors' Justification Processes on Their Decisions: A Cognitive Model and Experimental Evidence - Peecher, Mark E. (Journal of Accounting Research, 1996)
Mark E. Peecher, The Influence of Auditors' Justification Processes on Their Decisions: A Cognitive Model and Experimental Evidence, Journal of Accounting Research, Vol. 34, No. 1 (Spring, 1996), pp. 125-140